Pengembangan E-LKPD Interaktif Berbasis Wizer.me dalam Pembelajaran Pendidikan Pancasila di MINU Waru 1 Sidoarjo (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2025)
This research aims to answer the challenges in learning Pancasila education by developing interactive E-LKPD based on wizer.me. Through the application of the ADDIE development model and involving experts, this product has been successfully developed and validated. The interactive E-LKPD obtained validation from material experts of 84% and media experts of 88.57%, both of which were in the "very valid" category. Teacher responses showed practicality of 98.57%, and student responses reached 78.64%. Effectiveness testing shows an increase in student learning outcomes with an average pretest score of 75.18 increasing to 82.18 in the posttest. Hypothesis testing using paired sample t-test produces a Sig value. (2-tailed) of 0.001 (< 0.05), which indicates a significant increase. The research results show that this E-LKPD not only fulfills aspects of validity and practicality, but is also effective in increasing students' understanding of the concept of diversity in Indonesian society. This research makes an important contribution to the development of learning media that is innovative and relevant to the learning needs of the 21st century.